GERIATRIC ONSET OF PHEOCHROMOCYTOMA - Bernard, Dorothy Maria Anthony; Chua, Yi Jiang; Wong, Poh Shean; Hussein, Zanariah (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Elderly pheochromocytoma (age ≥65 years) is a rare phenomenon, however, there have been increased detection rates because of advances in imaging and longer life expectancy. At Putrajaya Hospital, there was a total of 60 cases of pheochromocytoma between 2013 to 2023, with only 10% (6 cases) being in the elderly category. CASE We present two cases of pheochromocytoma in the elderly who presented as adrenal incidentalomas. An 84-year-old Malay female with hypertension, type 2 diabetes mellitus(T2DM), and chronic kidney disease (CKD) stage 2 initially presented with palpitations, and was noted incidentally to have a right adrenal mass on abdominal ultrasound. Workup revealed elevated 24-hour urinary metanephrine 14.3 umol (0.33-1.53) and 24-hour urinary normetanephrine 4.6 umol (0.88-2.88). Adrenal CT revealed a well-defined right adrenal lesion measuring (3.5 x 3.2 x 3.4 cm) with plain HU +35. Patient underwent an uneventful open right adrenalectomy which revealed an adrenal tumour measuring 6.5 x 4 x 5 cm with capsular breach. She was discharged well after 6 days. Histopathology confirmed right adrenal pheochromocytoma with vascular and capsular invasion. Postoperatively, blood pressure was controlled on two antihypertensives with normal 24-hour urinary metanephrine and normetanephrine. A 71-year-old Chinese female with T2DM, hypertension, and CKD stage 5 presented with incidental findings of a right adrenal mass on abdominal ultrasound during CKD workup. 24-hour urinary metanephrine revealed elevated urinary metanephrine 19.56 umol (0.33-1.53) and 24-hour urinary normetanephrine 55.66 umol (0.88-2.88). Adrenal CT revealed a right adrenal lesion measuring 5.1 x 5 x 5.7 cm with plain HU +24. The patient underwent an uneventful right open adrenalectomy and was hospitalized for 4 days. Histopathology confirmed right adrenal pheochromocytoma measuring 6 x 5 x 5.5 cm with no capsular breach. Postoperatively, blood pressure was controlled on one antihypertensive with normal 24-hour urinary metanephrine and normetanephrine. CONCLUSION Screening for elderly pheochromocytoma should not be missed and these patients should be managed in highvolume endocrine surgery centres to minimize operative complication rates.